2017
DOI: 10.1007/s10561-017-9619-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimized decellularization protocol including α-Gal epitope reduction for fabrication of an acellular porcine annulus fibrosus scaffold

Abstract: Recent advances in tissue engineering have led to potential new strategies, especially decellularization protocols from natural tissues, for the repair, replacement, and regeneration of intervertebral discs. This study aimed to validate our previously reported method for the decellularization of annulus fibrosus (AF) tissue and to quantify potentially antigenic α-Gal epitopes in the decellularized tissue. Porcine AF tissue was decellularized using different freeze–thaw temperatures, chemical detergents, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 37 publications
0
40
0
Order By: Relevance
“…It has been accepted that the presence of α‐Gal will induce the rejection of porcine heart valves (Naso et al, ; Naso, Gandaglia, Iop, Spina, & Gerosa, ). It showed that the decellularization procedures could diminish the content of antigen (Wu et al, ). An Enzyme‐linked immunosorbent assay (ELISA) based quantitative method was used to assess the number of epitopes of native valves and decellularized valves (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been accepted that the presence of α‐Gal will induce the rejection of porcine heart valves (Naso et al, ; Naso, Gandaglia, Iop, Spina, & Gerosa, ). It showed that the decellularization procedures could diminish the content of antigen (Wu et al, ). An Enzyme‐linked immunosorbent assay (ELISA) based quantitative method was used to assess the number of epitopes of native valves and decellularized valves (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in vivo AF regeneration studies have resulted in mixed but suboptimal outcomes . Decellularized AF grafts applied in rat annuluotomy‐mediated AF‐defect rat model for AF repair resulted in large scar tissue formation . On the other hand, application of crosslinked collagen constructs applied in a rat needle‐puncture model, showed strongly enhanced IVD features compared to nontreated discs, but still reported atypical AF tissue organization .…”
Section: Discussionmentioning
confidence: 99%
“…The primary objective of decellularizing allogenic or xenogenic tissues for the creation of biomaterial scaffolds is to remove all cells, nuclear material and antigenic epitopes while maintaining critical ECM components, their spatial distribution, relative ratios, and tissue microarchitecture. 22,[28][29][30][31][32][33][34][35][36][37][38] This top-down approach to scaffold development aims to minimize the possibility of immune rejection while yielding a biomimetic scaffold that can promote targeted tissue regeneration. Moreover, this approach offers several advantages compared to building scaffolds from the ground-up including; (1) obtaining a "prefabricated," tissuespecific microarchitecture without employing complex additive manufacturing techniques, which (2) yields scaffolds that provide "built-in" instructional cues to local/seeded cells instructing them to attain tissue-specific phenotypes and contribute to tissue regeneration even in the absence of other exogenous soluble growth and differentiation factors.…”
Section: Discussionmentioning
confidence: 99%